Climate change profile of Pakistan. - Chaudhry, Qamar Uz Zaman (Asian Development Bank, 2017)
Catastrophic floods, droughts, and cyclones have plagued Pakistan in recent years. The 2010 flood killed 1,600 people and caused around 10 billion in damage. The 2015 Karachi heat wave led to the death of more than 1,200 people. Climate change related natural hazards may increase in frequency and severity in the coming decades. Climatic changes are expected to have wide-ranging impacts on Pakistan, affecting agricultural productivity, water availability, and increased frequency of extreme climatic events. Addressing these risks requires climate change to be mainstreamed into national strategy and policy. The profile covers (i) historical and future expected trends of climate change at provincial level, (ii) expected climate impacts on priority sectors, (iii) the institutional and policy frameworks to address climate change, (iv) climate finance sources, and (v) opportunities for adaptation.